The Actors and the Financial Affairs of the Northern Dimension - Ruotoistenmäki, Riikka; Babykina, Evgenia (Valtion taloudellinen tutkimuskeskus VATT, 2002)
This research describes the role of International Financial Institutions and the Financial Framework of the European Union in development of the Northern Dimension countries. It also describes the region as an operational environment. We have compared the loans disbursed to the region in 1990-1996 and 1997-2000, and their proportion of all loans has increased. Furthermore, co-operation in environmental projects has been taken forward in the form of Northern Dimension Environmental Partnership. Financing of projects in Northwest Russia present the greatest problem, as it is still rather insignificant and directed mostly to the most developed and richest regions. Due to these problems concerning the Northwest Russia, we have described more specifically the operational environment of this region. Tässä tutkimuksessa kuvataan kansainvälisten rahoituslaitoksien ja Euroopan unionin rahoitusjärjestelmien osuutta Pohjoisen ulottuvuuden maiden kehityksessä, sekä aluetta toiminnallisena ympäristönä. Alueelle suuntautuvia lainoja on vertailtu ajanjaksoilla 1990-1996 ja 1997-2000, ja alueen suhteellinen osuus kaikista maksetuista lainoista on kasvanut. Lisäksi yhteistyötä ympäristöhankkeiden alalla on lisätty. Suurimmat ongelmat ovat nähtävissä Luoteis-Venäjän projektien rahoituksessa, joka on vielä vähäistä ja suuntautuu lähes yksinomaan kehittyneimmille alueille. Luoteis-Venäjän ongelmien vuoksi tutkimuksessa on keskitytty tarkastelemaan erityisen tarkkaan juuri tämän alueen oloja.